POTENSI Enterolobium cyclocarpum (Willd.) Griseb DAN Centrosema pubescens Benth. SEBAGAI AKUMULATOR PENCEMAR MERKURI - Nuril Hidayati (BERITA BIOLOGI, 2012)
Some plant species growing in the contaminated areas, indicated high tolerance and potentially affective in accumulating pollutants. These plants can be utilized as hyper accumulators for cleaning up contaminated sites. This research aims to examine plants that grow under Hg contaminated media and to analyze their potency as hyper accumulators. Two pioneer plant species Enterolobium cyclocarpum (Willd.) Griseb and Centrosema pubescens Bent. that proven tolerant and dominant at contaminated sites of gold mine were examined in this research. The plants were grown in liquid media added with mercury (HgCl2) with different level of concentrations 0 ppm, 10 ppm and 20 ppm. Chelate Ammonium Thiosulphate [(NH4)2S2O3] was added with concentration levels of 0 ppm and 20 ppm. Plant performances, cellular responses, Hg accumulation in the plant were assessed. The results revealed that the growth of both plant species decreased with the increase of Hg contamination level. The presents of chelating agent improved adaptability of the plants, indicated by the increase of biomass production and Hg content in the plants, even at the highest level of Hg concentration (20 ppm). Cellular responses showed at 20 ppm Hg, indicated by the decrease of both the number and the size of epidermis and pith cells. Accumulation of Hg in the plants increased with the increased of Hg concentration in the media. Mercury accumulation in both plant species were more concentrated in the root system rather than the shoot.